Exploring the role of gain versus loss framing and point of reference in messages to reduce human–bear conflicts. Issue 2 (1st June 2018) - Lu, Hang; Siemer, William F.; Baumer, Meghan S.; Decker, Daniel J.
Abstract: As a fundamental social process, communication can help natural resource managers prevent or manage many human–wildlife conflicts, but research on how to present effectively information that contributes to the reduction of human–wildlife conflicts is scant. We examined the effectiveness of point-of-reference and gain-versus-loss framing in heightening intentions to prevent human–black bear conflicts. We randomly assigned 811 participants to one of six message conditions as part of a 3 (point of reference: family versus community versus bear) × 2 (message framing: gain versus loss) between-subjects factorial design or a control condition. The findings show that a match between loss framing and low-construal referencing point (e.g., family-referencing), and a congruency between gain framing and high-construal referencing point (e.g., bear-referencing) lead to higher risk perception and behavioral intentions. This study provides guidance for continuing research and design of risk communication in the context of human–bear conflicts.